Angiographic characteristics of coronary artery fistulas - Cemal Tuncer; Beyhan Eryonucu; Talantbek Batyraliev; Mustafa Gokce; Remzi Yilmaz; Murat Akkoyun; Gürkan Acar (Türk Kardiyoloji Derneği Arşivi, 2014)
Objectives: Coronary artery fistula (CAF) in adults is a rare form of coronary artery anomaly. It is often diagnosed incidentally during coronary angiography. The aim of this study was to evaluate the clinical and angiographic characteristics of adult patients with CAF. Study design: We retrospectively reviewed the database of 70,850 patients who had undergone coronary angiography in five different invasive cardiology centers in the southeastern region of Turkey. Among them, 56 patients had CAF (39 males, 17 females, mean age: 63.7+-10.4 years). Demographic data, clinical evaluation and cardiac catheterization reports were reviewed from the medical records. Results: A total of 58 fistulas were detected in 56 patients; two patients (3.6%) had bilateral fistulas originating from both the left and right coronary artery. In our angiographic series, CAF prevalence was 0.08%. Dyspnea on exertion and/or angina pectoris was the most common symptom (69%). Fifteen patients (26.8%) had concomitant obstructive coronary artery disease. Coronary artery fistulas originated mainly from the left anterior descending artery (n=30, 51.7%). Others originated from the right coronary artery (n=15, 25.9%), circumflex artery (n=6, 10.3%), and right sinus of Valsalva (n=3, 5.2%). In four patients (n=4, 7.1%), multiple micro fistula were draining into the left ventricle. Conclusion: In our angiographic series, the prevalence of CAF was 0.08%, and the most common site of origin was the left anterior descending artery.